New Encyclopedia of Southern Culture, v. 17. - Mohr, Clarence L. (University of North Carolina Press, 2011)
Offering a broad, up-to-date reference to the long history and cultural legacy of education in the American South, this timely volume of The New Encyclopedia of Southern Culture surveys educational developments, practices, institutions, and politics from the colonial era to the present. With over 130 articles, this book covers key topics in education, including academic freedom; the effects of urbanization on segregation, desegregation, and resegregation; African American and women's education; and illiteracy. These entries, as well as articles on prominent educators, such as Booker T. Washing.